Optimized Design of 1 700 V IGBT Field Limiting Ring and Field Plate Termination - Rongbin ZHOU; Ping YANG; Maosen TANG; Junhan YE; Jun SHEN; Dong LIU; Liheng ZHU (机车电传动)
The breakdown voltage is an important parameter for IGBT, and the breakdown voltage of the device is mainly related to the termination structure, so the research on the termination structure has always attracted attention. The termination structure of 1 700 V IGBT was designed in this paper. The termination technique combining field limiting ring and field plate could reduce the peak electric field on the device surface and improve the breakdown voltage. The termination structures with different field plate length and oxide thickness were simulated. Polynomial fitting and multiple regression were used to analyze the relationship between breakdown voltage and surface electric field distribution, the length of field plate on each ring and oxide thickness. Based on this, the breakdown voltage and surface electric field of the device could be predicted, and the time spending on termination design could be shortened. After adjustment, the breakdown voltage has achieved 1 927 V with 366 μm length on termination structure, and efficiency of the termination is 91.5%. The peak of surface electric field was effectively reduced and the surface electric field distribution was optimized.